Specificity of mystical discourse in humanities (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2023)
The article “The specifics of the mystical discourse in humanitarianism” presents the results of research into the essence of mysticism throughout its historical development in the context of philosophy, religious studies, and literature. The author understood the essence of the mystical in such fields of humanities as: philosophy and literary studies. Differences in the perception of mysticism in “Western” and “Eastern” philosophies are clarified. Attention is focused on the concepts of Ukrainian scientists who interpreted mysticism and mysticism in different ways. The concepts of "female mysticism", "Christian mysticism", "German mysticism", mysticism of the occult era, as well as modern mysticism are also analyzed. Their leading specific features, which developed and transformed depending on socio-cultural changes, are singled out. Concepts of mysticism of such philosophers as Meister Eckhart, V. Stace, V. James are outlined. An attempt was made to analyze mystical elements in myths and folklore, the connection of mysticism with mythopoetics and neomythologism in literature was considered. It has been established that interest in the mystical, as well as in the philosophy of existentialism, especially spreads in response to significant social changes, when values are reassessed and spiritual orientations change, it is the mystical experience that arouses special interest and acquires a mass character. It has been noticed that mysticism in literature, in particular, in Ukrainian, is now gaining considerable popularity. Authors of whimsical prose, mystical novels and short stories actively engage mystical experience as an anthropological mode. The origins of mystical images in literature can be seen in myths and in German literature of the 18th and 19th centuries (J. von Goethe, E. Hoffmann). The author of the article also drew attention to different classifications of demonological images in Ukrainian literature (classifications by V. Davydyuk, N. Levkovych, A.-D. Kryvenko), their specificity depending on different regions of Ukraine, the connection with holidays and special days for Ukrainians, as well as the fact that many images of Ukrainian mythology are characterized by ambiguity.
Keywords: mystic; mysticism; German mysticism; folklore images; demonological images